Plan de comunicación estratégico externo de una organización no gubernamental de Lima Metropolitana - Koo Mateo, Patricia María Isabel (2020)
The present communicational project intervened, during the months of April to September 2019, the external sphere of the non-governmental organization Educa.Impacta.Crece, focused in providing classes that develop the socio-emotional skills of students between six and eight years of IE Fe y Alegría N° 24 of Villa María Del Triunfo. After carrying out a holistic analysis and the development of a logical framework with the main objective of attracting 32 new volunteers for the 2019-2 semester, strategies and publication grids were done for its Facebook and Instagram pages, a manual of brand based on the pre-existing one, graphic and audiovisual pieces, as well as a brochure and an institutional presentation for conducting visits to attract new members and donor companies of food, classroom materials, economic goods and/or corporate volunteering. All the materials developed were approved by representatives of the institution and implemented in two phases. The first stage covered the months of April to July; the second, August and September. By Sept. 16, 2019, the expected goal had been achieved, confirming the success of the project.